Development of a community-based golf and exercise program for people with Parkinson's disease. (November 2018) - Cash, Megan F.; Ulanowski, Elizabeth; Danzl, Megan
Abstract: Individuals with Parkinson's disease (PD) typically display symptoms of rigidity, bradykinesia, and postural instability that can limit participation in recreational activities. The purpose of this clinical report is to describe the development, implementation, and outcomes of a novel and innovative community-based golf and exercise program for individuals with PD. In response to community interest, the program was developed through a unique partnership that blended the expertise of physical therapists and golf professionals. The 6-week program consisted of golf instruction and task-specific exercises. Improvements were noted in seven of eight participants for golf performance (driving distance and club head speed) and quality of life (PD Questionnaire-39) outcome measures. This report describes the design and implementation of a golf and exercise program for people with PD based on community need, evidence, and clinical expertise. Considerations and recommendations for future programs are discussed, such as program length, staffing, volunteers, funding, location, and resources.